USE OF INNOVATIVE TECHNOLOGIES IN TEACHING ENGLISH LANGUAGE TO PRIMARY EDUCATION STUDENTS - Ochilova Noila Farmonovna; Soliyava Malika Bobirshoyevna (Journal of new century innovations, 2023)
Abstract: The author of the article discusses the game as a method of teaching English lessons in primary classes. As a result, the author concludes that the game has a universality that allows you to adapt it to different goals and tasks. Game techniques perform many functions in the process of child development, facilitate the learning process, help to learn the increasing material every year and unobtrusively develop the necessary competencies.